How Product Knowledge Shapes the Impact of Artificial Intelligence on Spotify Brand Relationship and Loyalty - Kalyani, Meisianny Citta; Su, Kellyn; Putri, Jovannia Grisella Eka; Nizwan, Akira Gempita (APPS Publications, 2024)
The main focus of this research is to find out whether the use of Artificial Intelligence has an effect on Spotify’s Customer Brand Relationship and Customer Loyalty, on the other hand it is also mediated by Product Knowledge. This research uses quantitative methods which are distributed through questionnaires and processed using SmartPLS. Respondent requirements include (1) Spotify users, (2) aged 12 – 45 years, and (3) domiciled on the island of Java. The data analysis process involves validity testing which is considered relevant if the value is more than 0.5 (> 0.5), reliability testing which is considered relevant if the value is more than 0.7 (> 0.7), and hypothesis testing which is considered significant if it has value more than 1.96 (> 1.96). From a total of 195 respondents, the research results explain that the Artificial Intelligence variable influences Spotify’s Customer Brand Relationship and Customer Loyalty, which shows a positive and significant influence. Similar results were also obtained if mediation from Product Knowledge was added. Examining the impact of Artificial Intelligence specifically within the context of Spotify and its users is a relatively focused area. While AI is increasingly prevalent, research delving into its direct influence on customer brand relationships and loyalty for a specific digital service like Spotify might offer unique insights.